Localized α4 Integrin Phosphorylation Directs Shear Stress-Induced Endothelial Cell Alignment - Goldfinger, Lawrence E. (2008)
Vascular endothelial cells respond to laminar shear stress by aligning in the direction of flow, a process which may contribute to athero-protection. Here we report that localized α4 integrin phosphorylation is a mechanism for establishing the directionality of shear stress-induced alignment in microvascular endothelial cells. Within 5 minutes of exposure to a physiological level of shear stress, endothelial α4 integrins became phosphorylated on Ser(988). In wounded monolayers, phosphorylation was enhanced at the downstream edges of cells relative to the source of flow. The shear-induced α4 integrin phosphorylation was blocked by inhibitors of cAMP-dependent protein kinase A (PKA), an enzyme involved in the alignment of endothelial cells under prolonged shear. Moreover, shear-induced localized activation of the small GTPase Rac1, which specifies the directionality of endothelial alignment, was similarly blocked by PKA inhibitors. Furthermore, endothelial cells bearing a non-phosphorylatable α4(S(988)A) mutation failed to align in response to shear stress, thus establishing α4 as a relevant PKA substrate. We thereby show that shear-induced PKA-dependent α4 integrin phosphorylation at the downstream edge of endothelial cells promotes localized Rac1 activation, which in turn directs cytoskeletal alignment in response to shear stress.